Tourism Awareness Group Strategy in Strengthening Collective Action and Social Capital for Padang City Tourism Development - Dupa, Hendra; Ansofino, Ansofino; Irwan, Irwan (International Journal of Educational Research Excellence (IJERE), 2024)
The focus of the study in this research is to analyze the strategies of tourism awareness groups in strengthening collective action and social capital for the development of Padang City tourism. The theory used in this theory is the collective action theory put forward by Eggertsson and the social capital theory put forward by Putnam. This research uses a qualitative approach with a data analysis process using the ideas of Miles and Huberman. Data collection methods were carried out in several ways, namely: non-participant observation, interviews and document study. This research focuses on the strategies carried out by tourism awareness groups in tourism development by combining 2 theories. The results of this research are that tourism awareness groups in strengthening collective action carry out various strategies, namely: 1) The desire to increase and maximize tourism, 2) Having activities carried out together, 3) Coordinating between actors in developing city tourism, 4) Forming groups tourism awareness group among teenagers. Apart from that, the tourism awareness group also carries out strategies to strengthen social capital for tourism development, namely as follows : 1 ) Building trust between tourism awareness groups, 2) Expanding networks between tourism awareness groups, 3) Following the rules and norms within the tourism awareness group